Epidemiology of rheumatic heart disease in black shcoolchildren of Soweto, Johannesburg. Issue 5981 (23rd August 1975) - McLaren, M J; Hawkins, D M; Koornhof, H J; Bloom, K R; Bramwell-Jones, D M; Cohen, E; Gale, G E; Kanarek, K; Lachman, A S; Lakier, J B; Pocock, W A; Barlow, J B
Abstract : A survey to determine the prevalence of rheumatic heart disease (R.H.D.) in Black children was conducted in the creeches and primary schools of the South Western Townships of Johannesburg (Soweto). A total of 12 050 Black children were examined by 10 cardiologists in May to October 1972. The overal prevalence rate of R.H.D. was 6.9 per 1000, with a peak rate of 19.2 per 1000 in children of the seventh school grade. The maximal age incidence was 15-18 years and there was a female preponderance of 1 6:1. A rise in prevalence occurred with increasing family size. Most children (92%) were asymptomatic, and in 82.5% R.H.D. was diagnosed for the first time during the school survey. The commonest valve lesion was mitral regurgitation, which was present in 93% and occurred as an isolated lesion in 47.5%. Lancefield's group A beta-haemolytic streptococcus was isolated from the throats of 52 per 1000 Soweto children. The auscultatory features of a non-ejection systolic click and late systolic murmur were prevalent (13.9 per 1000) and had several epidemiological factors in common with R.H.D. A comprehensive preventative campaign is urgently needed in South Africa, directed at both primary and secondary prophylaxis of R.H.D. The socioeconomic status of the community must be improved if optimal prevention is to be achieved.